To mix or not to mix : efficient adaptation to windthrow risk - Hyyrynen, Matti; Lintunen, Jussi; Peltoniemi, Mikko (Institute of Physics Publishing, 2025)
Disturbance to spruce forests from wind and bark beetles is projected to worsen. It has been suggested that mixed-species forests could provide a more disturbance-resilient option than spruce monocultures. We used dynamic optimization to study how profitable mixed forests are compared to pure spruce forests by examining two similar neighboring stands facing a windthrow risk. We found that under high current windthrow risk levels in northeastern Finland, Norway spruce (Picea abies)-only forests are more profitable than mixed forests consisting of spruce and silver birch (Betula pendula). However, if the windthrow risk to spruce trees increases by 35% compared to its current level, and the risk level of birch remains at its current level, mixed forests become more profitable. When carbon is priced at €50 per ton of CO2, the additional income from carbon storage in mixed forests outweighs the economic advantage of spruce timber, making mixed forests more profitable—even if the risk to spruce increases by only 25%. Hence, mixed-species forests become increasingly profitable as carbon prices rise. Therefore, mixed-species forestry represents a cost-efficient strategy for adapting to increasing environmental risks and mitigating climate change.
Keywords: windthrow risk; mixed-species forests; carbon price; climate change adaptation; economic feasibility